The journey toward shared governance: the lived experience of nurse managers and staff nurses. (27th February 2013) - Ott, Joyce; Ross, Carl
<x xml:space="preserve">Abstract</x> Aims The purpose of the study was to explore the lived experience of nurse managers and staff nurses in shared governance. Background Shared governance refers to systems and services aligned in partnership. The information gained by studying the lived experience of nurse managers and staff nurses in shared governance is valuable for providing knowledge of empowerment. Methods A qualitative design was used. Data were collected through a semi‐structured interview using five questions with 11 Registered Nurses. Data were analysed through thematic analysis. Results Four themes emerged from data analysis. Nurse managers identified the journey of patient satisfaction; journey of empowerment; journey of self‐management and journey of wellness. Staff nurses identified the journey of development and implementation of best practice; journey to provide quality patient care, journey to a new culture of nursing; and journey of a variety of challenges. Conclusions This study supports the idea that collaboration between nurse managers and staff nurses develops a journey toward shared governance. Implications for nursing management Nursing management can use findings to empower nurses to collaborate with nurse managers toward best practice. This adds to current knowledge that partnership of nurse managers and staff nurses, supports and encourages ownership in shared governance.